Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

If $z=\int_0^x \sin(x-s)f(s) \, \mathrm ds$ can anyone explain to me how you would compute $z'=\frac{\mathrm d}{\mathrm dx}\int_0^x \sin(x-s)f(s) \, \mathrm ds$

Or in general $z'=\frac{\mathrm d}{\mathrm dx}\int_0^x \! f(s,x) \, \mathrm ds$? Thanks!

I considering using Leibniz's rule, but I don't know if it can be applied to this situation.

share|improve this question
1  
$\sin(x-s)=\sin(x)\cos(s)-\sin(s)\cos(x)$ –  pedja Oct 25 '11 at 12:45
add comment

3 Answers

up vote 4 down vote accepted

Looking at the wikipedia page of differentiation under the integral sign, you set $a(x) = 0$, $b(x) = x$ and $f(x, s) = \sin(x-s) f(s)$.

Alternatively, consider $z(x) = \int_0^x \sin(x-s) f(s) \mathrm{d} s$, and think of $z(x+ \delta x)-z(x)$:

$$ \begin{eqnarray} z(x+ \delta x)-z(x) &=& \int_0^{x+\delta x} \sin(x+\delta x-s) f(s) \mathrm{d} s - \int_0^x \sin(x-s) f(s) \mathrm{d} s \\ &=& \int_0^{x+\delta x} \sin(x+\delta x-s) f(s) \mathrm{d} s - \int_0^x \sin(x+\delta x-s) f(s) \mathrm{d} s + \\&& \int_0^x \sin(x+\delta x-s) f(s) \mathrm{d} s - \int_0^x \sin(x-s) f(s) \mathrm{d} s \\ &=& \int_{x}^{x+\delta x} \sin(x+\delta x-s) f(s) \mathrm{d} s + \int_0^x \left( \sin(x+\delta x -s) - \sin(x-s) \right) f(s) \mathrm{d} s \\ &\sim& \delta x \left( \sin(\delta x) f(x) + \int_0^x \cos(x-s) f(s) \right) \end{eqnarray} $$ In the limit $\lim_{\delta x \to 0} \frac{z(x+\delta x)-z(x)}{\delta x}$ the first term becomes zero, and you are get the answer: $$ z^\prime(x) = \int_0^x \cos(x-s) f(s) \mathrm{d} s $$

share|improve this answer
    
Excellent thanks! –  Freeman Oct 25 '11 at 16:45
add comment

A general approach to this type of problems might be this: think of $z$ as the composition of the two functions $f:\mathbb R ^2 \to \mathbb R$ and $g:\mathbb R \to \mathbb R ^2$:$$f(x,y)=\int _a ^y p(x,t)\text d t,\qquad g(x)=(x,x).$$ So $z(x)=(f\circ g)(x)$. Applying the chain rule (note that $g'=(1,1)$) you get: $$z'(x)=\partial _x f (x,x)+\partial _y(x,x),$$ so the answer is $$z'(x)=\int _a ^x \partial _x p(x,t)\text d t+p(x,x).$$

share|improve this answer
add comment

use general case of Leibniz integral rule. http://en.wikipedia.org/wiki/Differentiation_under_the_integral_sign

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.